2017
DOI: 10.1021/acs.jnatprod.7b00610
|View full text |Cite
|
Sign up to set email alerts
|

Lamellodysidines A and B, Sesquiterpenes Isolated from the Marine Sponge Lamellodysidea herbacea

Abstract: Four new sesquiterpenes, lamellodysidines A and B, O,O-dimethyllingshuiolide A, and 11-epi-O,O-dimethyllingshuiolide A (1-4), were obtained from the marine sponge, Lamellodysidea herbacea, collected in Indonesia. Their planar structures were elucidated by analysis of spectroscopic data. The absolute configurations of the new compounds were determined by the calculated ECD spectra. Compound 1 has a unique carbon framework, and 2 is a new nitrogenous sesquiterpene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Therefore, the current primary issues in marine conservation, such as the loss of biodiversity through over-exploitation and habitat degradation, can be overcome. Additional information can be found in the Supplementary Materials [95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current primary issues in marine conservation, such as the loss of biodiversity through over-exploitation and habitat degradation, can be overcome. Additional information can be found in the Supplementary Materials [95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,…”
Section: Discussionmentioning
confidence: 99%
“…Strong NOESY correlations of overlapped proton signals at δ H 2.00 and δ H 5.11 suggested that these three groups of double-bonds Δ 6,7 , Δ 10,11 , and Δ 14,15 were all E -geometry. Furthermore, the absolute stereochemistry of C-21 can be determined by following the determination method of O , O -dimethyllingshuiolide A [ 13 ]. The characteristic positive Cotton effect at 253 nm in the CD spectrum of 1 was virtually identical to that of the simplified models (detailed in the Supplementary Information S1 ), ( S )-5-hydroxy-4-methylfuran-2(5 H )-one (4 S - 8 ) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several new terpenes were isolated from Indonesian marine sponges from the Dictyoceratida order (Figure 6), such as L. herbacea [36], Spongia sp. [37], and Carterospongia foliascens [38].…”
Section: Compound Compound Class Species Biological Activity Refmentioning
confidence: 99%